2021
DOI: 10.4028/www.scientific.net/ddf.406.319
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Automatic TIG Welding Parameters of AISI 304L ASS Welds Using Response Surface Methodology

Abstract: The present study, aims to investigate, under welding parameters of current, voltage and gas flow, the effects of welding parameters on tensile strength of AISI 304L ASS welds using response surface methodology (RSM). The RSM and variance analysis (ANOVA) were used to check the validity of quadratic regression model and to determine the significant parameter affecting tensile strength of welds. Hence, ANOVA clearly revealed that the contribution of each factor is 71.40% of voltage, 19.2% of current and 8.30% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…The figure 1 illustrates that the hardness value for the fusion zone falls within the range of values for the heataffected zone and the base material. This is in agreement with previous researches [16,17]. Consequently, the hardness gaps (ΔH316LN, ΔHP11) between the highest and lowest levels were selected to achieve optimal welding parameters and to ensure the reliability of the welded structure.…”
Section: Rsm Toolssupporting
confidence: 87%
See 1 more Smart Citation
“…The figure 1 illustrates that the hardness value for the fusion zone falls within the range of values for the heataffected zone and the base material. This is in agreement with previous researches [16,17]. Consequently, the hardness gaps (ΔH316LN, ΔHP11) between the highest and lowest levels were selected to achieve optimal welding parameters and to ensure the reliability of the welded structure.…”
Section: Rsm Toolssupporting
confidence: 87%
“…Where, δ stringers have grown and raised near the diffusion line. This growth of δ stringers is attributed to fast cooling rate of austenite grain induced by ferritic transformation to austenite (α → γ + δ) during the thermal welding cycle, consequently retaining a heightened proportion of ferrite represented by δ stringers [16,30]. Furthermore, It is observed that suboptimal parameter gives thick branches of δ phase in FZ and HAZ with dendritic morphology in the most FZ, while an OP parameter weld results in thin branches of δ phase with vermicular morphology of austenite in FZ (figures 9(a), (c)).…”
Section: Evolution Of Op and Sop Parameters 321 Effect Of Parameters ...mentioning
confidence: 99%
“…Most of the research on the fusion welding of FSS focuses on TIG welding, GMA welding, and SMAW processes. However, information concerning the optimization of TIG welding process parameters need be more analyzed using experimental designs that is in Taguchi and RSM methods [16,17]. Thus, the main objective of this study is to optimize the welding parameters for AISI 430 FSS welds by Taguchi's design focused on minimization of ferrite grains size in the fusion zone.…”
Section: Introductionmentioning
confidence: 99%